Patient perceptions of phage therapy for diabetic foot infection. - Katherine E Macdonald; Helen J Stacey; Gillian Harkin; Lesley M L Hall; Matthew J Young; Joshua D Jones (PLoS ONE)
Infections of diabetic foot ulcers are common, generally recalcitrant and often complicated by antibiotic resistance. Alternative antimicrobial strategies are needed. Phage therapy is a promising alternative that is being rediscovered. Despite phage therapy's 100-year history, there have been no investigations into patient thoughts and concerns. This study aimed to explore patient awareness of and concern about antibiotic resistance and gain insight into the perceptions of phage therapy among a patient group that could potentially benefit from phage therapy. Patients with an active or resolved (healed or amputated) diabetic foot ulcer were eligible to participate. A survey was distributed digitally to eligible patients across Scotland via the NHS Research Scotland Diabetes Network and hard copies were available in diabetic foot clinics at the Royal Infirmary of Edinburgh and Queen Elizabeth University Hospital, Glasgow. A focus group of five survey respondents was held in Glasgow. Fifty-five survey responses were obtained. There was a high level of awareness (76.4%; N = 55) and concern (83.3%; N = 54) about antibiotic resistance. While largely aware of viruses, most patients had not heard of phage or phage therapy. Patients were no more concerned about phage than antibiotic therapy, with most suggesting more information could alleviate any concerns. Patient acceptability of phage therapy was high, a finding confirmed by the focus group. Patients are concerned about antibiotic resistance and supportive of 'new' antimicrobials. We have demonstrated that patients are supportive, enthusiastic and accepting of phage therapy. Although 'Western' phage therapy remains in its infancy, an understanding of patient ideas, concerns and expectations will be important in eventually shaping and successfully reintroducing phage therapy.